Pengaruh Kompetensi Kewirausahaan dan Orientasi Kewirausahaan Terhadap Kinerja Usaha di Mediasi Keunggulan Bersaing Pada Usaha Milenial Kopi Keliling di Kota Jambi - Devi, Naulia Pitaloka Candra; Dahmiri, Dahmiri; Ihsan, Moh. (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study was to determine and analyze the influence of entrepreneurial competence and entrepreneurial orientation on business performance in the mediation of competitive advantage in the Millennial Coffee Business in Jambi City. The analysis tool used is Partial Least Squares analysis. Based on the results of the study, it can be concluded that entrepreneurial competence and entrepreneurial orientation have a positive and significant effect on competitive advantage and business performance of Coffee Business owners or partners in Jambi City. The higher the entrepreneurial competence and orientation, the greater the competitive advantage achieved, which ultimately has a positive impact on improving business performance. Competitive advantage has been proven to be a mediating variable that strengthens the relationship between entrepreneurial competence and orientation on business performance, so it is important for business actors to continue to develop entrepreneurial skills and innovative spirit in order to maintain and improve their business competitiveness.